Nanoliposomes containing limonene and limonene-rich essential oils as novel larvicides against malaria and filariasis mosquito vectors - Alireza Sanei-Dehkordi; Mohammad Djaefar Moemenbellah-Fard; Mostafa Saffari; Elham Zarenezhad; Mahmoud Osanloo (BMC, 2022)
Abstract Background Mosquito-borne diseases such as malaria and encephalitis are still the cause of several hundred thousand deaths annually. The excessive use of chemical insecticides for transmission control has led to environmental pollution and widespread resistance in mosquitoes. Botanical insecticides' efficacies improvement has thus received considerable attention recently. Methods The larvicidal effects of three essential oils from the Citrus family and limonene (their major ingredient) were first investigated against malaria and filariasis mosquito vectors. An attempt was then made to improve their efficacies by preparing nanoliposomes containing each of them. Results The larvicidal effect of nanoformulated forms was more effective than non-formulated states. Nanoliposomes containing Citrus aurantium essential oil with a particle size of 52 ± 4 nm showed the best larvicidal activity (LC50 and LC90 values) against Anopheles stephensi (6.63 and 12.29 µg/mL) and Culex quinquefasciatus (4.9 and 16.4 µg/mL). Conclusion Due to the green constituents and high efficacy of nanoliposomes containing C. aurantium essential oil, it could be considered for further investigation against other mosquitoes' populations and field trials.